Digital Storytelling Islami: Inovasi Media Bimbingan Konseling untuk Pengembangan Kecerdasan Linguistik Siswa - Rendra Hendarsyah; Ulfah Ulfah; Muhamad Yasin; Ipan Fauzi; Imas Hayati (Fakultas Tarbiyah dan Kegurusn Universitas Islam Bandung, 2025)
This research addresses the low linguistic competence of elementary school students based on the Kemendikbudristek report (2023). The research objective is to develop Islamic-nuanced digital storytelling media for guidance and counseling services. The method used is Research and Development (R&D) with the ADDIE model, involving fifth-grade students of SDN Lagadar 01 through tests, interviews, and questionnaires. Expert validation results show a score of 4.64 (on a 5.00 scale), practicality of 85%, and effectiveness evidenced by a significant increase in linguistic intelligence (initial score: 62.4; final score: 83.6; p<0.001). The conclusion confirms that this media is a valid, practical, effective innovation that contributes to the integration of Islamic values in digital-based guidance and counseling services.